THE STUDY OF LANGUAGE FEATURES OF INDOGLISH AT JAKARTA INTERNATIONAL UNIVERSITY - Rahmawati, Debora; Rivalny, Agnechia Friska (Universitas Stikubank (UNISBANK) Semarang, 2025)
Indoglish (Indonesian English) is becoming the language that is mostly used by Indonesian people. The urgency of English skills encourages people to use English. However, not everyone fluently speaks English due to several factors such as the influence of their first language. This study aims to find the language features of Indoglish, especially in an international university environment with varied cultural backgrounds of Indonesian students. This study also explores the language features of Indoglish by focusing on characteristics in variations which might hinder intelligibility. The features include errors in verb tense markers, auxiliary verbs or verb phrases, active/passive forms, singular/plural noun markers, noun phrase structure, and part of speech. The data were collected from conversations among junior and senior students majoring in English Literature at Jakarta International University. Observation and note-taking were employed in this research to acquire the data. Data analysis was conducted using a descriptive qualitative method. The findings were presented in the form of an analysis of students’ utterances that contained Indoglish features. Therefore, this research contributed to filling the gap in Indoglish studies within international academic settings and helped raise awareness among readers about Indoglish features that are often unconsciously uttered in Indonesia. This research resulted in the students uttering all those 6 features mentioned by Endarto, with the most used feature is Singular/Plural Error in Indonesian English, and the least used is Active/Passive voice in Indoensian English. The researcher also found that another error was massively repeated by the Students. Keywords: Language Features, Language Variation, Indoglish, International Environment, Intelligibility